2015
DOI: 10.1007/s10068-015-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Skin whitening activity of supercritical fluid extract from spent coffee in B16F10 melanoma cell

Abstract: In the present study, we evaluated the skin whitening effects of supercritical fluid extract (SFE) of the spent coffee (SC) on tyrosinase inhibition activity, melanin synthesis inhibition activity and DOPA staining. Hot water extracts from coffee bean (CB) and SC and drip extracts from CB were employed for control. Inhibitions of melanin activities of SFE (SC) at short processing time were significantly higher than other values under the same extract processing. In comparison, inhibition of melanin activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
4
5
0
1
Order By: Relevance
“…The results also yielded evidence of eicosenoic, behenic, and lignoceric acids that were present at below 1% of the oil. The results are in agreement with those reported by Sung et al (2015) on Vietnamese coffee. [8] It is noted that studies conducted by Jenkins et al (2014) and Dang and Nguyen (2019) indicated fatty acid composition of SCG obtained from Vietnamese coffee was different with respect to weight percentages of palmitic, oleic, and linoleic acids.…”
Section: Oil Content and Fatty Acid Compositionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results also yielded evidence of eicosenoic, behenic, and lignoceric acids that were present at below 1% of the oil. The results are in agreement with those reported by Sung et al (2015) on Vietnamese coffee. [8] It is noted that studies conducted by Jenkins et al (2014) and Dang and Nguyen (2019) indicated fatty acid composition of SCG obtained from Vietnamese coffee was different with respect to weight percentages of palmitic, oleic, and linoleic acids.…”
Section: Oil Content and Fatty Acid Compositionsupporting
confidence: 93%
“…[3][4][5][6][7] Spent coffee ground is also used for development of skin-whitening products due to its inhibition of tyrosinase activity and melanin synthesis. [8,9] Sufficient amounts of dietary fiber, protein, lipid, and low glycemic sugars in SCG and acceptable rheological properties of SCG-supplemented dough give rise to its application in biscuit products. [10] In addition, SCG reportedly contains a wide variety of bioactive constituents that can be exploited as a nutraceutical or used in food products.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study has shown that the SFC from spent coffee exhibited significantly high activities in the inhibition of melanin synthesis and tyrosinase activity [ 14 ], which is in accordance with our results. The authors concluded that high fatty acid content did not correspond with the capacity to inhibit melanin synthesis or tyrosinase activity.…”
Section: Discussionsupporting
confidence: 93%
“…The inhibitory effects of spent coffee grounds SFE on melanogenesis were reported by Sung et al [ 14 ]. However, the action mechanisms of spent coffee grounds for depigmentation still remained to be elucidated.…”
Section: Introductionmentioning
confidence: 68%
“…Besides, stearic and oleic acid are found to be present in the oil, at the levels of 10 and 15 g/g, respectively. The results are in agreement with prior research on Vietnamese coffee by Sung et al (2015) (Sung, Jung, Sin, Kim, & Wee, 2015). Linoleic acid is a polyunsaturated fatty acid found abundantly in vegetable oil.…”
Section: Fatty Acidssupporting
confidence: 92%